Assessment of Revised Recruitment Standards for Asthma in the Australian Defence Force. Issue 11 (1st November 2014) - Ireland, Renee; Waller, Michael; MacKenzie, Alison; Peake, Jonathan; Nasveld, Peter
ABSTRACT: Objective: To assess the impact of relaxed asthma recruitment standards adopted by the Australian Defence Force in 2007. Methods: A retrospective audit was conducted on clinical and administrative data for recruits, with and without mild asthma, in their first year of service. Results: There was no evidence that mild asthmatics experienced worse outcomes than nonasthmatic recruits. Mild asthmatics had fewer illnesses and restricted duty days and were less costly compared to other recruits. There was no difference in the rate of discharge (attrition) between those with and without mild asthma. Conclusions: The revised recruitment standards for asthma in the Australian Defence Force have not resulted in unanticipated medical or administrative costs to the organization. Health and administrative outcomes differed little between mild asthmatics and nonasthmatic recruits in their first 12 months of service.